Star of the Sea : farewell to old Ireland / Joseph O'Connor. - O'Connor, Joseph, 1963- (Vintage, 2019)
During winter 1847, the Star of the Sea sets sail from Ireland for New York. Among the refugees are a maidservant, bankrupt Lord Merridith, an aspiring novelist and a maker of revolutionary ballads. Each is connected more deeply than they know. But a killer is stalking the decks, hungry for vengeance.